2012
DOI: 10.2147/eb.s21841
|View full text |Cite
|
Sign up to set email alerts
|

Primary headache disorders and neuro-ophthalmologic manifestations

Abstract: Headache is an extraordinarily common complaint presenting to medical practitioners in all arenas and specialties, particularly primary care physicians, neurologists, and ophthalmologists. A wide variety of headache disorders may manifest with a myriad of neuro-ophthalmologic symptoms, including orbital pain, disturbances of vision, aura, photophobia, lacrimation, conjunctival injection, ptosis, and other manifestations. The differential diagnosis in these patients is broad and includes both secondary, or symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Acute headache following ischemic stroke is more commonly associated with infarction of the posterior than the anterior cerebral circulation. Moreover, subcortical and lacunar infarctions are the least associated with acute headache compared to cortical strokes 16,17 . Previous studies have reported that vessels in the posterior circulation are more richly innervated by nociceptive afferents than in the anterior circulation 17‐20 .…”
Section: Headache Attributed To Cranial or Cervical Vascular Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Acute headache following ischemic stroke is more commonly associated with infarction of the posterior than the anterior cerebral circulation. Moreover, subcortical and lacunar infarctions are the least associated with acute headache compared to cortical strokes 16,17 . Previous studies have reported that vessels in the posterior circulation are more richly innervated by nociceptive afferents than in the anterior circulation 17‐20 .…”
Section: Headache Attributed To Cranial or Cervical Vascular Disordermentioning
confidence: 99%
“…Moreover, subcortical and lacunar infarctions are the least associated with acute headache compared to cortical strokes 16,17 . Previous studies have reported that vessels in the posterior circulation are more richly innervated by nociceptive afferents than in the anterior circulation 17‐20 . Pain signals from the circle of Willis are transmitted through the trigeminal nerve, whereas vasculature structures of the posterior fossa are innervated by the cervical plexus, vagus, and trigeminal nerve 18,20,21 .…”
Section: Headache Attributed To Cranial or Cervical Vascular Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Substance P, nitrous oxide, calcitonin generated peptides have been suspected as chemical effectors in the possible pathophysiological mechanisms of retinal migraine, by exercising a non-desired effect leading to the plasma extravasation, neurogenic inflammation, vasodilatation. Other neuro-ophthalmological structures involved are: periaqueductal gray (PAG), locus coeruleus (LC), dorsal Raphe nucleus (DRC), retinal vasculature, and activation of the retinal-thalamic-visual pathway [ 3 ].…”
Section: Pathophysiological Effectors and Mechanismsmentioning
confidence: 99%
“…Although there is a strong consensus that migraine begins with cortical hyperexcitability followed by spreading waves of compensatory inhibition throughout the cortical surface,1 evidence also points to the trigeminovascular system and its associated subcortical and neuro-ophthalmologic manifestations as the etiological source for migraine 27. Whether vasogenic or neurogenic in origin, numerous studies have investigated visual pathway operations in an attempt to identify the pathogenesis of migraine through its characteristic visual symptoms such as triggers, visual snow, halos, phosphenes, paliopsia, and photophobias 7. Interestingly, many of the hallucinatory symptoms have been identified as stable geometric fortifications (ie, Kluver’s forms8) that scale out to the same hexagonally packed cortical hypercolumns of the cortex 9.…”
Section: Introductionmentioning
confidence: 99%